PERANCANGAN SISTEM INFORMASI PEMESANAN PRODUK PERCETAKAN BERBASIS WEB PADA DEPOK PRINTING - Rizki Mauludi, - (2019)
Printing services are one of the services that are very important for the business world, specially for corporate business people, event organizers, students, and students. Printing services make it easy for humans to print such as books, brochures, newspapers, and magazines. The demand for printing services has recently experienced a significant increase in the need for printing brochures, banners or banners in large numbers for certain events, so in this case the ease of ordering is needed. With the development of increasingly sophisticated information technology and ordering products still being done manually it is considered less effective. As faced by the ordering system at Depok Printing today. The ordering system is still done manually which requires consumers to come directly to Depok Printing printing so that it is considered to be less effective. For this reason, a web-based product ordering information system is needed to facilitate consumers in ordering. The development tool used by researchers, namely PHP as an application interface and MySQL as its database. The system development method uses the PIECES method with modeling namely UML (Unifed Modeling Language). With the development of ordering product information, printing products are expected to facilitate consumers in the ordering process